Prevalence of Anxiety, Depression and Job Dissatisfaction Among Healthcare Professionals: A Comparative, Cross-sectional Study in Bangladesh - Trisha, Samina Yesmin; Hossen, Md Shafiul; Hossan, Aiman; Eyakin, Sazaratul; Ibrahim, Mohammed (International Journal of Human and Health Sciences (IJHHS), 2025)
Background: Healthcare professionals are more likely to have the anxiety and depression that may affect the wellbeing and workforce sustainability. Objective: To find out the prevalence of anxiety, depression and job dissatisfaction among Bangladeshi healthcare professionals. Methods: This comparative, cross-sectional study was conducted on 600 participants – 402 healthcare professionals as cases and 198 non-healthcare workers as controls. Physicians (120), nurses (122) and pharmacists (160) were included as healthcare professionals. A semi-structured questionnaire was developed. General Anxiety Disorder-7 (GAD-7) was used to measure anxiety, while Patient Health Questionnaire-9 (PHQ-9) scale was used to determine the severity of depression. Job dissatisfaction was assessed by Employee Satisfaction Index (ESI) with slightly modification. Results: A higher prevalence of anxiety (mild:40.80%, moderate:13.93% and severe:14.43%), depression (mild:40.30%, moderate:18.91%, moderately severe:11.94%, and severe:3.98%) and job dissatisfaction (22.39%) were observed among healthcare professionals than in non-healthcare workers. Elevated risk of the occurrence of mild (p=0.009) and severe (p=0.002) anxiety, mild (p<0.001), moderate (p=0.001) and moderately severe (p=0.006) depression were also observed in healthcare professionals. Based on score, the higher risk of anxiety (p<0.001), depression (p=0.019) and job dissatisfaction (p<0.001) were recorded in pharmacists compared with that of physicians and nurses. A significant association of anxiety and depression with job dissatisfaction was also explored only in pharmacists. Besides, gender and job-experience of the professionals contributed to the anxiety and depression (p<0.05). Conclusion: Bangladeshi healthcare professionals, particularly pharmacists, had the higher rate of anxiety, depression, and job dissatisfaction. However, more research with a large sample size is required to validate our study. International Journal of Human and Health Sciences Vol. 09 No. 01 Jan’25 Page: 33-41